Exporting Analysis of the Small and Medium Enterprises (SMEs) in the Mukdahan Special Economic Zone - Thamwicha, Wanwisa; Chaiprasit, Kanokporn (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2017)
This study aims to analyze the export investment of the Small and Medium Enterprises (SMEs) in Mukdahan Special Economic Zone. The Qualitative research was conducted by employing content analysis from related literature such as journal, research article and other academic documents. To gain in-depth insights, interviews with the SMEs exporters in Mukdahan special economic zone were also conducted. Descriptive analysis was used to analyze the responses from the interviews. The research results revealed that Mukdahan special economic zone had a high trading potential with People's Democratic Republic of Lao (the PDR). The SMEs in this area were domestic exporters who exported goods to neighbor countries, particularly the PDR. Concurrently, the SMEs in the PDR also order goods from the SMEs in Mukdahan province. This context motivated the SMEs in the Mukdahan special economic zone to adopt themselves to respond to the environmental trading changes in terms of developing the accession of each business operating stage. This practice may lead to successful business deals in terms of the continuous increase of export values in the future.